2007
DOI: 10.1007/s11747-007-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of opportunism in exchange relationships

Abstract: The potential to engage in opportunism is a central theme in institutional economics, yet prior research has not quantitatively reviewed the role of opportunism in marketing research. This study uses meta-analytic techniques to synthesize research on opportunism conducted over the last quarter century. The analysis of 183 effect sizes extracted from 54 publications from the period 1982 to 2005 offers some support to extant channel theory. The research also indicates that the informant's frame of reference and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(173 citation statements)
references
References 52 publications
5
165
0
1
Order By: Relevance
“…Behavioral uncertainty refers to difficulties in evaluating a partner's performance following a contractual agreement (Crosno & Dahlstrom, 2008). In that occasion, the firm can be exploited by the partner (Crosno & Dahlstrom, 2008 performance.…”
Section: Behavioral Uncertainty and Retailers' Commercial Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral uncertainty refers to difficulties in evaluating a partner's performance following a contractual agreement (Crosno & Dahlstrom, 2008). In that occasion, the firm can be exploited by the partner (Crosno & Dahlstrom, 2008 performance.…”
Section: Behavioral Uncertainty and Retailers' Commercial Practicesmentioning
confidence: 99%
“…In that occasion, the firm can be exploited by the partner (Crosno & Dahlstrom, 2008 performance. Based on these points, we hypothesize that:…”
Section: Behavioral Uncertainty and Retailers' Commercial Practicesmentioning
confidence: 99%
“…When the decision-making authority is concentrated at the top management, rank-and-file employees have little autonomy in daily operations (Hage & Aiken, 1967). By limiting their discretion, centralization is likely to restrain inter-member and intra-organizational opportunistic propensity (Bunderson & Boumgarden, 2010;Crosno & Dahlstrom, 2008), so that a centralized organization may enhance trust among rank-and-file employees and reduce transaction costs in knowledge exchange within a firm (Argyres & Silverman, 2004;Chesbrough & Teece, 2002;Dwyer & Oh, 1987). The enhanced trust among organizational members will strengthen their commitment and cooperation between one another (Morgan & Hunt, 1994).…”
Section: Os Information Flow and Behavior Changementioning
confidence: 99%
“…Further, volume uncertainty, which is created by poor forecasting of future demand patterns, is reduced by sharing of strategic information between retailers and manufactures like future new products, retail stores, and customer preferences (Eksoz et al 2014;Mukhopadhyay and Setaputra 2011). Long-term collaboration can protect companies from opportunistic behaviour (Crosno and Dahlstrom 2008). Cao and Zhang (2011) studied the impact of supply chain collaboration on performance of US manufacturing firms and found that collaborative advantage mediates the relationship between supply chain collaboration and firm performance for small firms while it partially mediates the relationship for medium and large firms.…”
Section: Transaction Cost Economicsmentioning
confidence: 99%
“…As a result of an extensive literature review in the initial phase of this study, the following factors were examined: Logistics information management (Chouinard et al 2005;Ramirez, 2012), close-loop capability (Bernon et al 2011;Jayant et al 2012), integration capability (Dwyer et al 1987;Liu et al 2013), coordination capability (Cao and Zhang 2011;Crosno and Dahlstrom 2008) institutional incentives (Polák and Drápalová 2012;Franke et al 2006), and conformity capability (Assavapokee and Wongthatsanekorn 2012) were identified.…”
Section: Contributions To the Current Supply Chain Literaturementioning
confidence: 99%